Berpikir Lateral Dalam Bisnis - Soegiono, Soegiono (potensio, 2008)
The lateral thinking concept for the first time promoted by EdwardsDe Bono from result deep studying about human attitude in takingdecision. The thinking of De Bono are multipled or promoted bymany industrialists or entrepreneurs or businessmen to pile upstrategic trading or business to winning in competition in trading orbusiness. So that the lateral thinking sees something with mannerlooking that good and attract. Manner looking that inconventionallateral thinking becomes attractive because the differenceperformens each others. Braving the difference performens revealsthe new innovation that created at the market. The competition withusing the lateral thinking design are competition completely eachother in the industries. So between competitors in competition cando trade and business manner solidly.Key Words : The lateral thinking in business